Spin Seebeck in the weakly exchange-coupled Van der Waals antiferromagnet across the spin-flip transition - He, Xue; Ding, Shilei; Giil, Hans Gløckner; Wang, Jicheng; Bhukta, Mona; Wu, Mingxing; Shi, Wen; Lin, Zhongchong; Liang, Zhongyu; Yang, Jinbo; Kläui, Mathias; Brataas, Arne; et al. (Nature communications, 2025)
Spin Seebeck effect refers to the creation of spin currents due to a temperature gradient in the magnetic materials or across magnet-normal metal interfaces, which can be electrically detected through the inverse spin Hall effect when in contact with heavy metals. It offers fundamental insights into the magnetic properties of materials, including the magnetic phase transition, static magnetic order, and magnon excitations. The behavior of the spin Seebeck effect across the spin-flop transition has been extensively studied, whereas the spin Seebeck effect across the spin-flip transition remains poorly understood. Here, we demonstrate the spin Seebeck effect in a weakly exchange-coupled van der Waals antiferromagnet CrPS 4 . The spin Seebeck effect increases as the magnetic field increases before the spin-flip transition due to the enhancement of the thermal spin current as a function of the applied field. A peak of spin Seebeck effect is observed at the spin-flip field, which is related to the magnon mode edges across the spin-flip field. Our results extend spin Seebeck effect research to van der Waals antiferromagnets and demonstrate an enhancement of spin Seebeck effect at the spin-flip transition. The authors find the magnon spin transport in CrSP 4 /Pt (Ta) can be effectively modulated through adjustments in temperature and applied magnetic field, particularly at the spin-flip field.